ICOS ATC Meteo Release from Norunda (100.0 m), 2017-06-17–2026-03-31 - Irene Lehner; Meelis Molder (Integrated Carbon Observation System, 2026)
Quality-controlled meteo data
Lehner, I., Molder, M. (2026). ICOS ATC Meteo Release from Norunda (100.0 m), 2017-06-17–2026-03-31, ICOS RI, https://hdl.handle.net/11676/0hOnNM1ReZABkDIKAw5CQulx
Keywords: Atmosphere Thematic Centre; ICOS; meteo; time instant, UTC; time instant, UTC; air temperature; air temperature; standard deviation of air temperature; standard deviation of air temperature; number of points; number of points; quality flag; quality flag; relative humidity; relative humidity; standard deviation of relative humidity; standard deviation of relative humidity; wind speed; wind speed; standard deviation of wind speed; standard deviation of wind speed; wind direction; wind direction; standard deviation of wind direction; standard deviation of wind direction; air pressure; air pressure; standard deviation of air pressure; standard deviation of air pressure; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap